Cultural Mapping and Heritage Trail in Kuala Kangsar - Mohd Yunus, Nor Mazlan; Hj. Endut, Esmawee; Said, Shahrul Yani (Journal of Social Transformation and Regional Development, 2021)
Kuala Kangsar is the Royal Town of Negeri Perak. It was established in the 1720s. The name Kuala Kangsar is believed to be derived from the kangsar plant (Hibiscus flocussus) that grows in abundance along the banks of the Sungai Kangsar. Another strong suggestion claims that the name was handed down by explorers and settlers who had established a settlement at the mouth of the river. They called their new home Kuala Kurang Sa, a short form for Kuala Kurang Seratus because there were 99 tributaries that flowed into the Sungai Perak around the area. Kuala Kangsar became famous and remarkable not only because of its title as a royal town but also for its heritage and historical factors. There are a lot of heritage assets in this area. Because of these reasons, Kuala Kangsar has become popular and appealing to attract more tourists. This paper will identify and classify the heritage assets in Kuala Kangsar. The identifications and classifications will be based on some methods which consist of site familiarisation, unstructured interviews, visual observation and literature reviews. After heritage assets identification is done, this paper will develop the Cultural Mapping for Kuala Kangsar where Cultural Mapping is a tool to illustrate all the heritage assets’ location and position in mapping and graphics. Finally, this paper will introduce the Heritage Trail to link all these heritage assets in Kuala Kangsar.